2018
DOI: 10.1128/jcm.01874-17
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of High-Throughput Nanofluidic PCR-Based Pneumococcal Serotyping and Quantification Assays Using Sputum Samples for Diagnosing Vaccine Serotype Pneumococcal Pneumonia: Analyses by Composite Diagnostic Standards and Bayesian Latent Class Models

Abstract: The lack of reliable diagnostic tests for detecting vaccine serotype pneumococcal pneumonia (VTPP) remains a challenging issue in pneumococcal vaccine studies. This study assessed the performances of high-throughput nanofluidic PCR-based pneumococcal serotyping and quantification assay methods using sputum samples (the nanofluidic sputum quantitative PCR [Sp-qPCR] assay) to diagnose 13-valent pneumococcal conjugate VTPP compared with the performance of the serotype-specific urinary antigen detection (UAD) assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In addition, other studies have found that PCR did not show significant increase in either sensitivity or specificity in pneumococcal pneumonia, even when quantification was included [3841]. In this regard, Stralin et al [42] and Kakiuchi et al [43] obtained high sensitivity and specificity using PCR assays for S. pneumoniae applied to sputum and nasopharyngeal aspirate samples in patients with CAP. Moreover, protected specimen brush and bronchoalveolar lavage quantitative cultures added nearly 30% more microbiological documentation for CAP compared to sputum cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies have found that PCR did not show significant increase in either sensitivity or specificity in pneumococcal pneumonia, even when quantification was included [3841]. In this regard, Stralin et al [42] and Kakiuchi et al [43] obtained high sensitivity and specificity using PCR assays for S. pneumoniae applied to sputum and nasopharyngeal aspirate samples in patients with CAP. Moreover, protected specimen brush and bronchoalveolar lavage quantitative cultures added nearly 30% more microbiological documentation for CAP compared to sputum cultures.…”
Section: Discussionmentioning
confidence: 99%
“…PPSV23 coverage in patients with PP was reported in 5 studies [34,35,54,56,57]. In these studies, the coverage decreased from 63.7% to 54.1% during the study period (2008e2016) in patients aged 16 years [57]; was 68.2% among those aged 61e79 years [56]; and was the lowest (8.2%) among those aged 22e99 years [35].…”
Section: Pp (Ppsv23 Coverage)mentioning
confidence: 95%
“…Mortality rate was in the range of 4.5%e25.0% in 4 studies in patients with PP [22,31,34,35]. Among patients aged 70.4 ± 14.6 years and 22e99 years, death was reported in 34/ 135 (25%) patients [22] and 11/244 (4.5%) patients, respectively [35].…”
Section: Ppmentioning
confidence: 97%
See 1 more Smart Citation
“…It can amplify nucleic acid molecules from one to several million in a very short period of time (usually in tens of minutes), so it is regarded as the most important molecular biology technology today. It plays an important role in the fields including next-generation high-throughput sequencing and clinical nucleic acid marker detection [1][2][3][4][5][6][7][8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%